Small customers, big market : commercial banks in microfinance - Harper, Malcolm, 1935-; Arora, Sukwinder Singh; Energy and Resources Institute (Warwickshire, UK : ITDG Pub. ; New Delhi : The Energy and Resources Institute, 2005)
This books shows commercial bankers that they can profitably provide microfinance services to the poor. It illustrates, through the experience of particular banks, why banks have become involved and how they made a success of their investment.
Includes bibliographical references (p. [299]-301) and index.
osa 03/02/05
Loans
Keywords: Microfinance -- Case studies; Bank loans -- Case studies; Banks and banking -- Case studies